2024
DOI: 10.1001/jamainternmed.2023.8225
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19−Associated Acute Kidney Injury and Longitudinal Kidney Outcomes

Abinet M. Aklilu,
Sanchit Kumar,
James Nugent
et al.

Abstract: ImportanceCOVID-19 infection is associated with a high incidence of acute kidney injury (AKI). Although rapid kidney function decline has been reported in the first few months after COVID-19−associated AKI (COVID-AKI), the longer-term association of COVID-AKI with kidney function remains unknown.ObjectiveTo assess long-term kidney outcomes of patients who had COVID-19−associated AKI.Design, Setting, and ParticipantsThis was a retrospective longitudinal multicenter cohort study conducted in a large hospital sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Reasons why the cause of CKD are not different from elsewhere in the world might as follows: The clinical trial was conducted during the COVID-19 pandemic period when many patients, especially older patients, couldn’t have access to effective medical treatments. According to published data, numerous studies [ 20–22 ] have reported COVID-19 infection is associated with a high incidence of AKI or A on C; In addition, the limited number of patients (98 cases) included in this clinical trial also had a certain impact on the results; Besides, the influence of regional reasons also has a certain relationship. The presence of CKD poses a threat to kidney function and delays the recovery of kidney function in patients with AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons why the cause of CKD are not different from elsewhere in the world might as follows: The clinical trial was conducted during the COVID-19 pandemic period when many patients, especially older patients, couldn’t have access to effective medical treatments. According to published data, numerous studies [ 20–22 ] have reported COVID-19 infection is associated with a high incidence of AKI or A on C; In addition, the limited number of patients (98 cases) included in this clinical trial also had a certain impact on the results; Besides, the influence of regional reasons also has a certain relationship. The presence of CKD poses a threat to kidney function and delays the recovery of kidney function in patients with AKI.…”
Section: Discussionmentioning
confidence: 99%
“…It has been discussed that the biochemistry of kidney tubular injury plays a pivotal role in the pathogenesis of long COVID [ 52 ]. Recently, a multicenter cohort study ( n = 9624 patients) concluded that survivors of hospitalization with AKI-associated COVID-19 experienced a 33% lower risk of major adverse kidney events and 69% lower risk of mortality in comparison with AKI related to influenza or other illnesses [ 53 ]. Patients were followed up for a maximum of 2 years after hospital discharge.…”
Section: Kidney Disease and Long Covidmentioning
confidence: 99%
“…Akliu et al's research [31] demonstrated a notable decrease in major adverse kidney events (MAKE) among patients with COVID-19-associated AKI, with an adjusted hazard ratio for MAKE of 0.67, indicating a significantly lower risk when compared to AKI from other illnesses. This was further supported by a marked reduction in all-cause mortality, with an adjusted hazard ratio (aHR) of 0.31, and a lower rate of worsened kidney function (aHR, 0.78) in the COVID-AKI group.…”
Section: Literature Findingsmentioning
confidence: 99%